Janzen–Connell effects partially supported in reef‐building corals: adult presence interacts with settler density to limit establishment. Issue 8 (21st June 2021) - Sims, Carrie A.; Sampayo, Eugenia M.; Mayfield, Margaret M.; Staples, Timothy L.; Dalton, Steven J.; Gutierrez‐Isaza, Nataly; Pandolfi, John M.
Abstract : In many plant and sessile marine invertebrate (SMI) taxa, population and community dynamics are heavily influenced by processes occurring during the dispersal and establishment phases. The Janzen–Connell (J–C) hypothesis predicts increased survival of early life stages with decreasing conspecific density and increased distance from conspecific adults. Evidence of J–C effects in maintaining diversity is common in plant communities, but its importance in SMI communities remains unclear. Under controlled aquarium conditions, we examined the effect of density‐dependence and adult conspecific water treatments (absent/present) on propagule settlement success and settler post‐settlement survival, along with associated spatial patterns, for six broadcast‐spawning, reef‐building coral species from three families. We also tested if settlement success was linked to increasing propagule species diversity for three coral species from two families. We found that the probability of settlement was density independent and not influenced by adult present water treatments. Yet, adult present water treatments and settler density did have a synergistic negative effect on the probability of short‐term settler survival for all species examined. Settlers also showed greater spatial aggregation as their numbers increased, but were less aggregated in adult present water treatments compared to those in adult absent water treatments. We further show evidence of significant species interactions among propagules, as settlement in single‐species trials was four‐fold higher compared to mixed‐species trials. Our findings from controlled experimental arenas indicate that the early establishment of corals was predominantly limited by density‐dependent settler–adult interactions among conspecifics and propagule–propagule interactions among heterospecifics. Thus, the proximity to established conspecific adults, settler density and species diversity of propagules are relevant drivers of local coral community diversity and structure. Based on these outcomes, we suggest that the J–C hypothesis, with demonstrated importance for plants, is partially upheld for reef corals.